Disability, Enhancement, and Flourishing. Issue 5 (21st November 2022) - Eberl, Jason T
Abstract: Recent debate among bioethicists concerns the potential to enhance human beings' physical or cognitive capacities by means of genetic, pharmacological, cybernetic, or surgical interventions. Between "transhumanists, " who argue for unreserved enhancement of human capabilities, and "bioconservatives, " who warn against any non-therapeutic manipulation of humanity's natural condition, lie those who support limited forms of enhancement for the sake of individual and collective human flourishing. Many scholars representing these views also share a concern over the status and interests of human beings with various types of cognitive and physical disabilities, some of which may be ameliorable by enhancement interventions. The question addressed in this paper is whether valuing the enhancement of human capabilities may be reconciled with valuing the existence and phenomenological experiences of human beings with various disabilities. Can we value enhanced capabilities without disvaluing those whose capabilities fall below a defined threshold of "normal function"? Furthermore, if certain forms of disability, particularly cognitive disabilities, negatively impact one's flourishing, could the enhancement of one's cognitive capacities through biotechnological means enhance one's flourishing.